2010
DOI: 10.1016/j.freeradbiomed.2010.02.038
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide blocks cellular heme insertion into a broad range of heme proteins

Abstract: Although heme insertion into proteins enables their function in bioenergetics, metabolism, and signaling, the mechanisms and regulation of this process is not fully understood. We developed a means to study cellular heme insertion into apo-protein targets over a 3 h time period, and then investigated how nitric oxide (NO) released from a chemical donor (NOC-18) might influence heme (protoporphyrin IX) insertion into seven targets that present a range of protein structure, heme ligation, and function (three NO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
67
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 109 publications
0
67
0
Order By: Relevance
“…More recently, we showed that NO can inhibit cellular heme insertion into a broad range of mammalian proteins, including all three NOS enzymes, hemoglobin, catalase, and cytochrome P450 (17). Importantly, the mechanism of NO action did not involve changes in heme availability or effects of NO on cellular energy production or activation of soluble guanylate cyclase (17). The results implied that NO might act on an uncharacterized yet common cellular component or process to generally inhibit heme insertion into proteins.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…More recently, we showed that NO can inhibit cellular heme insertion into a broad range of mammalian proteins, including all three NOS enzymes, hemoglobin, catalase, and cytochrome P450 (17). Importantly, the mechanism of NO action did not involve changes in heme availability or effects of NO on cellular energy production or activation of soluble guanylate cyclase (17). The results implied that NO might act on an uncharacterized yet common cellular component or process to generally inhibit heme insertion into proteins.…”
mentioning
confidence: 84%
“…In that study, the NO was produced naturally by iNOS in cells and was found to act somewhere near or at the point of heme insertion. More recently, we showed that NO can inhibit cellular heme insertion into a broad range of mammalian proteins, including all three NOS enzymes, hemoglobin, catalase, and cytochrome P450 (17). Importantly, the mechanism of NO action did not involve changes in heme availability or effects of NO on cellular energy production or activation of soluble guanylate cyclase (17).…”
mentioning
confidence: 94%
“…Stock solutions of novobiocin were prepared in water whereas 3-isobutyl-1-methylxanthine (IBMX) and radicicol were dissolved in DMSO. Stock solutions of hemin were freshly prepared in 0.1 N NaOH (32). cDNAs for human hsp90β and D88N-hsp90β mutant were gifts from Bill Sessa (Yale University, New Haven, CT).…”
Section: Methodsmentioning
confidence: 99%
“…RLF-6 cells were cultured in Ham F-12 K media containing L-glutamine and pyruvate, 5,000 U/L of penicillin/streptomycin and 20% (vol/vol) FBS. Heme depletion was achieved by culturing cells with 400 μM SA for 48 h before transfection or activation of sGC (30,32). RFL-6 cells expressing endogenous sGC were activated by NO donor SNAP (50 μM) or with heme-dependent (BAY 41-2272; 10 μM) or heme-independent activators (BAY 60-2770; 10 μM) from 0 to 30 min as indicated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation